Common fixed point results in F-metric spaces with application to nonlinear neutral differential equation - Hanadi Zahed; Ahmed Al-Rawashdeh; Jamshaid Ahmad (AIMS Mathematics, 2023)
The aim of this article is to obtain common fixed point results for generalized contractions involving control functions of two variables in the context of F-metric spaces. We also furnish an example to show the originality of our main result. Some results in the context of F-metric space equipped with a directed graph G are also established. As an application, we discuss the existence of solution to nonlinear neutral differential equation.